Kelas Keawetan Papan Zephyr Pelepah Sawit sebagai Bahan Bangunan dari Serangan Rayap - Lusita Wardani; Muhamad Yusram Massijaya; Yusuf Sudo Hadi; I Wayan Darwaman (Jurnal Teknik Sipil, 2016)
Zephyr board is a composite board that can be made from oil palm petiole, the waste from oil palm plantation. One of the noteworthy qualities of the composite board is its resistance to termite attacks. The purpose of this study was to analyze the resistance of zephyr board made from oil palm petiole to the attacks of dry wood termite (Cryptothermes spp Holmgreen) and subterranean termite (Coptothermes spp Light). Zephyr boards fed on termite consisted of the zephyr boards non-finishing and the ones with finishing. The results for the resistance of the zephyr boards to subterranean termite attack showed that the zephyr board which was made using adhesive of urea formaldehyde and phenol formaldehyde without finishing materials was in class IV while the zephyr board with finishing was classified as class I. The test for resistance of zephyr board with non-finishing to dry wood termite attack indicated that the board belonged to class II while the board with finishing was in class I. The tests were carried out using SNI 01.7207 2006.